Isolation and characterization of specific bacteriophage Va1 to Vibrio alginolyticus - Fernández Espinel, Carla (2017)
Vibrio alginolyticus is associated with diseases in aquaculture. The misuse of antibiotics has led to the search for alternatives in the treatment of bacterial diseases, among them the application of bacteriophages that infect and destroy bacteria selectively. In this way, a highly lytic V. alginolyticus bacteriophage, termed Va1, was isolated, with the aim to evaluate its physical chemical parameters. For this purpose, different temperature, pH, chloroform exposure and host range conditions were evaluated. The temperature stability of phage Va1 showed higher titers at 20 and 30 °C decreasing from 40 °C. With respect to pH, the highest titers for the bacteriophage were between 5 and 8, and chloroform exposure reduced viability of the Va1 phage by 25%. The one-step curve determined that the latency period and the burst size were 20 minutes and 192 PFU / infective center respectively. Under the transmission electron microscope, the Va1 phage showed an icosahedral head and a non-contractile tail, belonging to the Podoviridae family. In conclusion, Va1 phage presents potential characteristics for use in phage therapy.